BOOK REVIEW: Critical Realism: Basics and Beyond, by Hubert Buch-Hansen & Peter Nielson, Sept. 2020. London, Macmillan, 2020 - Choudhury, Masud (Journal of Critical Realism in Socio-Economics (JOCRISE), 2024)
This book provides a review of the book “Critical Realism: Basics and Beyond”, by Hubert Buch-Hansen & Peter Nielson, Sept. 2020. London, Macmillan pp. 168 (ISBN 978 1 352 01065 7). This is an original contribution, explained in informative content and written in clear language that is accessible to knowledgeable readers